Strategic Climate Policy in Small, Open Economies - Mads Greaker; Knut Einar Rosendahl (Statistics Norway, Research Department, 2006)
According to environmental interests groups governments should use their climate policy strategically in order to provide for a faster introduction of new, cleaner technologies. Strategic use of climate policy could also induce the development of a successful upstream abatement technology industry like the Danish windmill industry. Interestingly, this latter question has not been analyzed theoretically before. Our point of departure is a three-stage game between a government in a small country with a climate restriction, and a limited number of firms supplying carbon abatement technology. The government moves first, and may use its climate policy strategically to influence the behavior of the upstream technology firms. An especially stringent climate policy towards the polluting downstream sector may then in fact be well founded. It will increase the competition between the technology suppliers, and lead to lower domestic abatement costs. However, to our surprise, a strict environmental policy is not a particularly good industrial policy with respect to developing new successful export sectors.
Keywords: O32; Q2; Q25; 330; Strategic climate policy; Abatement technology; Small; open economies